Chapitre 6. Le déploiement de la médecine génomique: la place de l’autonomie du patient dans la réutilisation des données génétiques au profit de la recherche - Feriol, Lisa (Journal international de bioéthique et d'éthique des sciences, 2023)
Genetic research today is largely based on the reuse of data from care for the benefit of research. This evolution of practices, which involves an increasingly marked communication between care and research, questions the place given to the patient seen as a potential participant in research. In order to promote the circulation of genetic data generated and to allow their reuse for the benefit of different research, the French legislator reaffirmed the use of the opt-out mechanism ("non-opposition") in the last bioethics law of the 2 August 2021. If the reasons that led the legislator to make this shift from the concept of consent to the opt-out mechanism are legitimate, the conditions of implementation of this mechanism seem to need to be questioned in order to ensure the effectivity of the balance sought by the legislator between preserving the autonomy of the individual with regard to the sharing of his/her genetic data and encouraging the development of medical knowledge; one should not be to the detriment of the other.